Dante and Islam - Ziolkowski, Jan M., 1956- (Book collections on Project MUSE., 2015)
"Dante put Muhammad in one of the lowest circles of Hell. At the same time, the medieval Christian poet placed several Islamic philosophers much more honorably in Limbo. Furthermore, it has long been suggested that for much of the basic framework of the Divine Comedy Dante was indebted to apocryphal traditions about a "night journey" taken by Muhammad. Dante scholars have increasingly returned to the question of Islam to explore the often surprising encounters among religious traditions that the Middle Ages afforded. This collection of essays works through what was known of the Qur'an and of Islamic philosophy and science in Dante's day and explores the bases for Dante's images of Muhammad and Ali. It further compels us to look at key instances of engagement among Muslims, Jews, and Christians"--